2007
DOI: 10.1016/j.molcel.2007.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Structural Aspects of RbfA Action during Small Ribosomal Subunit Assembly

Abstract: Ribosome binding factor A (RbfA) is a bacterial cold shock response protein, required for an efficient processing of the 5' end of the 16S ribosomal RNA (rRNA) during assembly of the small (30S) ribosomal subunit. Here we present a crystal structure of Thermus thermophilus (Tth) RbfA and a three-dimensional cryo-electron microscopic (EM) map of the Tth 30S*RbfA complex. RbfA binds to the 30S subunit in a position overlapping the binding sites of the A and P site tRNAs, and RbfA's functionally important C termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
112
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(133 citation statements)
references
References 61 publications
11
112
2
Order By: Relevance
“…A recent publication (Goto et al 2011) has reported a functional interplay between YjeQ and RbfA during maturation of the 30S subunit. RbfA is a small protein that binds the 30S subunit at the junction of the head and body, and its binding alters the position of helices 44 and 45 (Datta et al 2007). Interestingly, RbfA seems to promote the association of YjeQ to the 30S subunits, and binding of YjeQ stimulates the dissociation of RbfA from the small subunit (Goto et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication (Goto et al 2011) has reported a functional interplay between YjeQ and RbfA during maturation of the 30S subunit. RbfA is a small protein that binds the 30S subunit at the junction of the head and body, and its binding alters the position of helices 44 and 45 (Datta et al 2007). Interestingly, RbfA seems to promote the association of YjeQ to the 30S subunits, and binding of YjeQ stimulates the dissociation of RbfA from the small subunit (Goto et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…16S RNA bridges B5 and B6 have intersubunit contacts on the 30S subunit contributed entirely by helix 44. Helix 44 has been shown to be organized late during the assembly of the 30S subunit and has been found to be disordered (18,19) or distorted (20)(21)(22) in structures of some of the assembly intermediates of the small subunit from various species.…”
Section: Significancementioning
confidence: 99%
“…Structurally, it has been shown that YjeQ, RbfA, and Era all bind in close proximity to the decoding center of the mature 30S subunit (Sharma et al 2005;Datta et al 2007;Guo et al 2011;Jomaa et al 2011b), suggesting that these factors play a joint role in the organization of the functional core of the small subunit. Genetic evidence suggests that RimM binds to a distinct region of the head of the 30S subunit comprised of helices 31 and 33b of the 16S rRNA and r-proteins S13 and S19 right above the decoding center (Lovgren et al 2004).…”
Section: Introductionmentioning
confidence: 99%